2002
DOI: 10.1055/s-2002-20289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study Comparing Bleeding and Nonbleeding Rectal Varices

Abstract: The prevalence of hemorrhage from rectal varices was significantly higher in patients with rectal varices of advanced form and/or with a positive "red color" sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Concerning the prediction of hemorrhage from rectal varices, Shudo et al reported that the prevalence of hemorrhage was significantly higher in patients with rectal varices of form and/or with a positive "red color (RC)" sign [1] . However, the RC sign is observed in only 40% of rectal varices [3] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the prediction of hemorrhage from rectal varices, Shudo et al reported that the prevalence of hemorrhage was significantly higher in patients with rectal varices of form and/or with a positive "red color (RC)" sign [1] . However, the RC sign is observed in only 40% of rectal varices [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of rectal varices varies among different reports (3.6-9%) [1,2] , accounting for 10% or less of patients with portal hypertension. According to a nationwide survey of ectopic varices in Japan from 2001 to 2005, rectal varices were the most common type of ectopic varices; the number of patients with rectal varices was 77 [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of haemorrhage from anorectal varices is significantly increased in larger varices and in patients with high-risk stigmata such as a positive "red colour" sign [26]. There is no evidence to suggest that the incidence of bleeding is increased with the presence of oesophageal variceal bleeding, a history of previous treatment of oesophageal varices or the aetiology of portal hypertension [6,26].…”
Section: Pathophysiology Aetiology and Prevalence Of Anorectal Varicesmentioning
confidence: 99%
“…Their prevalence in patients with cirrhosis is between 38% and 56%, whereas their prevalence in extrahepatic portal vein obstruction was reported between 63% and 94% [3,5] . Despite the high prevalence of rectal varices, clinically significant bleeding is rare and occurs in 0.5%5% of patients [6] . While the management of esophageal varices has been well established [7] , the optimal treatment of rectal varices remains to be determined.…”
Section: Introductionmentioning
confidence: 99%